Contribution of Economic Growth, Demography, Human Capital Quality, and Unemployment to Poverty Dynamics - Harnani, Sri (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This study aims to analyze the effects of economic growth, demography, human resource quality, and unemployment on poverty levels in East Java Province. The research seeks to understand these factors' role in shaping regional poverty dynamics. The study adopts a quantitative approach, utilizing statistical data analysis to examine the relationships between variables. The Indonesian Central Bureau of Statistics (BPS) data includes figures on economic growth, demography, human resource quality, unemployment, and poverty levels. Multiple linear regression analysis was employed to evaluate the influence of these independent variables on poverty. The findings indicate that economic growth does not significantly affect poverty levels in East Java, suggesting that growth has not been equitably distributed among income groups. Demography significantly impacts poverty, implying that better economic capacity and purchasing power reduce poverty. Conversely, human resource quality positively and substantially influences poverty, reflecting the challenges in competitiveness and skills among the population. Unemployment does not dramatically impact poverty, as income from other family members likely mitigates its effects. These findings align with previous studies and underscore the need for policies that promote inclusive economic growth and human capital development. The results highlight the importance of targeted policies to address poverty in East Java. Efforts should focus on equitably distributing economic benefits, enhancing human resource quality through education and skill development, and optimizing demographic potential. Policymakers and stakeholders must collaborate to develop sustainable strategies that address the complex interplay of economic and social factors driving poverty.